Advances in the design of ITK inhibitors. (April 2013) - Charrier, Jean-Damien; Knegtel, Ronald MA
<x xml:space="preserve">Abstract</x> Introduction: ITK is a member of the Tec family of nonreceptor protein tyrosine kinases that plays a central role in T-cell signaling. Its inhibition is seen as an attractive approach to the treatment of immune-mediated disorders. Insight into the function of ITK has emerged from studies on ITK-deficient mice, which exhibit defects in T-cell receptor (TCR) signaling and immune responses to pathogens. Although knockout studies provide an important contribution to the understanding of ITK inhibition, they have limitations in predicting the viability of small-molecule ITK inhibitors as therapeutic agents. Areas covered: Since the original publication of the structural information on the ITK enzyme, there have been a number of reports disclosing the discovery of ITK inhibitors from various chemical scaffolds. The authors present and describe the approaches followed by the various research groups in the field. An assessment of the various chemical tools available to the scientific community is also discussed, both from a biochemical and a structural point of view. Expert opinion: The majority of currently available ITK inhibitors either lack comprehensive selectivity data or evidence of their ability to effectively suppress T-cell signaling in cells or animal models. Although inhibitors targeting an inactive conformation of ITK have yielded the predicted phenotype, it remains unclear to what extent the observed biological activity is due to inhibition of the kinase activity of ITK. With available biological data suggesting the possibility of functional redundancy of ITK, the suitability of ITK as a potential molecular target for the development of new immunosuppressant drugs remains to be confirmed.